Pembelajaran Ilmu Sosial Berbasis Lingkungan sebagai Upaya Meningkatkan Kesadaran Sosial Siswa Sekolah Dasar - Anna Maria Oktaviani (Journal of Humanities, Social Sciences, and Education, 2025)
Social Studies (IPS) learning in Elementary Schools plays an important role in shaping the character and social awareness of students from an early age. This study aims to review the literature on the effectiveness of the environment-based learning approach in increasing the social awareness of elementary school students. The study was conducted by reviewing various relevant previous research results, both from accredited national journals and other scientific sources in the last five years. The results of the literature study show that environment-based learning is able to link IPS concepts with the realities of students' lives around them, thereby fostering social awareness, responsibility, and understanding of local social problems. Activities such as environmental observations, field studies, and community-based collaborative projects have proven effective in strengthening students' active involvement in learning. In addition, teachers who are able to utilize the potential of the environment as a learning resource can create a more contextual and meaningful learning experience. Thus, this approach can be used as an alternative strategy in IPS learning to increase students' social awareness. This article recommends the need for training for teachers in designing and implementing environment-based learning systematically and sustainably.